(untitled) (Singaporean Journal of Business Economics and Management, 2013)
Today, Employee empowerment is consider as important issues in human resource management organizations and In this regard, it is important that each of the individuals feel about their competence.Human resources consider as strategic asset of the organization And empowerment of employees, is a new approach in order to human resource development that cause increase productivity improve quality, and profitability of products and services of organizations. In order to achieve this goal and to help researchers and managers in the areas Human resources in this article is try to empower the patterns, the importance of this issue in organizations to explain.